Consequences for the Contralateral Limb: Multifactorial Risk Factors, Biomechanical Overload, and Structural Degeneration Following Achilles Tendon Rupture: A Narrative Review - Radliński, Michał; Palacz, Jakub Paweł; Papciak, Kinga Zofia; Woźniak, Klaudia; Jabłońska, Urszula Zofia; Gardzielik, Aleksandra; Korowaj, Karolina; Dercz, Maciej Piotr; Fitas, Alicja; Głaszczka, Michał (Quality in Sport, 2026)
Background. Long-term functional deficits are a harsh reality after an acute Achilles tendon rupture (ATR). Standard care usually targets just the torn tissue. The problem is that it completely ignores the wider biomechanical chain. When calf weakness persists, patients develop a major asymmetry in how they move. As a result, the opposite, seemingly healthy leg is forced to take on an excessive and chronic mechanical burden. Aim. To identify mechanisms of compensatory overload, evaluate biomechanical and structural changes in the contralateral healthy limb, and assess psychological factors following a unilateral ATR. Material and methods. A PubMed literature review synthesized clinical, systematic, and biomechanical studies (2012-2026). The analysis evaluated the bilateral impact of ATR, focusing on compensatory kinematics, psychological barriers, and morphological alterations in the uninjured tendon. Results. Athletes subconsciously shift their kinematics to shield the repaired tendon. This abnormal load redistribution, driven by a lack of psychological readiness, prevents the restoration of limb symmetry. Consequently, the contralateral limb suffers chronic, unphysiological overload. Objective imaging confirms this stress causes silent structural degeneration in the asymptomatic tendon, manifesting as morphological hypertrophy on ultrasonography and pathological tissue softening on sonoelastography. Conclusions. A unilateral ATR initiates a bilateral pathological cascade. Driven by psychological barriers and altered biomechanics, the healthy limb undergoes chronic loading and structural degeneration, elevating the risk of a contralateral rupture. Return-to-play algorithms must adopt a holistic bilateral paradigm integrating neuromuscular symmetry training, psychological screening, and routine imaging of the asymptomatic tendon.